Recent advances in the message passing interface 18th European MPI Users' Group Meeting, EuroMPI 2011, Santorini, Greece, September 18-21, 2011, proceedings - European MPI Users' Group Meeting 2011 Santorini, Greece); Cotronis, Yiannis 1952-.; SpringerLink (Online service). (Berlin New York Springer, 2011)
This book constitutes the refereed proceedings of the 18th European MPI Users' Group Meeting on Recent Advances in the Message Passing Interface, EuroMPI 2011, held in Santorini, Greece, in September 2011. The 28 revised full papers presented together with 10 posters were carefully reviewed and selected from 66 submissions. Topics covered are communication; I/O; networking, and implementation issues and improvements; algorithms and tools; interaction with hardware; applications and performance evaluation; fault and tolerance.
International conference proceedings.
Electronic reproduction.
Keywords: Parallel programming (Computer science) -- Congresses; Parallel processing (Electronic computers) -- Congresses; Electronic books